Short Communication: Qualitative determination of secondary metabolic compounds and macro-nutrients some botanical pesticide plants of East Kalimantan, Indonesia - INCE RADEN; SUYADI SUYADI; THAMRIN THAMRIN (Smujo International, 2016)
Abstract. Raden I, Suyadi, Thamrin. 2016. Qualitative determination of secondary metabolic compounds and macro-nutrients some botanical pesticide plants of East Kalimantan, Indonesia. Nusantara Bioscience 8: 141-144. The existence of natural alternative inputs for crop husbandry was considered as important resource of good agricultural practices to attend an environmentally friendly agricultural management. There are numerous potential plants for botanical pesticide used native in East Kalimantan, and those plants have been used by farmer to pest control, but they didn't know secondary metabolic compound and macronutrient in the plants. Pest control and soil fertility management were two main problems of agricultural development in East Kalimantan. This study aims to determine various secondary metabolic compounds and macronutrients content of six botanical pesticide plants, i.e. marigold (Tagetes erecta L.), neem tree (Azadirachta indica L.), sweet flag (Acorus calamus L.), brotowali (Tinospora crispa L.), soursop (Annona muricata L.), and golden trumpet vine (Allamanda cathartica L.). Some laboratory analysis were implemented in the study, variables used to determine secondary metabolic compounds were flavonoids; steroids; alkaloid; tannins; triterpenoids; and saponins, while, variables used to determine macronutrients were Nitrogen, Phosphorus, Potassium, Magnesium, and Calcium. Results showed that all of six botanical pesticides evaluated in this study were containing potential secondary metabolic compounds (SMC), soursop leaves containing three kinds of SMC (flavonoids, steroid, and tannin), whereas golden trumpet vine leaves only containing one kind of SMC (tannin), and the other four botanical pesticides (marigold, neem tree, sweet flag, and brotowali) containing two kinds of SMC (flavonoids and tannin). Furthermore, based on macronutrients content analysis, marigold contains macronutrient higher than other plants as liquid fertilizer source followed by neem tree, soursop, and sweet flag.